Novel sustained-release of Stryphnodendron obovatum leaves extract using natural rubber latex as carrier - Felipe Azevedo Borges; Paula Ratsue Siguematsu; Rondinelli Donizetti Herculano; Catarina Santos (São Paulo State University (UNESP), 2016)
Natural rubber latex biomembranes (NRL), obtained from rubber tree Hevea brasiliensis (Willd. ex A. Juss.) Mull. Arg., have been used as sustained drug release of drugs and plant extracts with medicinal properties. The Stryphnodendron obovatum Bench (Fabaceae), popularly known as "barbatimão" has anti-inflammatory and healing properties already described in literature. Thus, the aim of this work were to study the release behavior of the hydroethanolic extract from the leaves of S. obovatum loaded in the NRL by ultraviolet-visible spectroscopy (UV-VIS). The release followed a bi- exponential pattern and the mechanism of release was Super Case II (n > 1). FTIR analyses did not show reaction between NRL and extract, only intermolecular interaction. From SEM was possible to observe the extract at the surface, responsible for the initial fast release, which the concentrations at 5.0 mg/mL released 2.4% and at 0.1 mg/mL released 96.8%; both reached the plateau in 7 days. Keywords: Stryphnodendron obovatum. Hevea brasiliensis. Sustained release. Barbatimão. Tannin. Natural rubber latex.